2019
DOI: 10.48550/arxiv.1902.03263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival and extinction of epidemics on random graphs with general degrees

Abstract: In this paper, we establish the necessary and sufficient criterion for the contact process on Galton-Watson trees (resp. random graphs) to exhibit the phase of extinction (resp. short survival). We prove that the survival threshold λ1 for a Galton-Watson tree is strictly positive if and only if its offspring distribution ξ has an exponential tail, i.e., Ee cξ < ∞ for some c > 0, settling a conjecture by Huang and Durrett [12]. On the random graph with degree distribution µ, we show that if µ has an exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Kim [15] used this method to give a sharp estimate on the k-core threshold of Erdős-Rényi random graphs. It turns out that the method can also be very useful in the study of G(n, µ) as shown in [2]. In this subsection, we introduce the algorithm and derive some properties that are used in Sections 2.2 and 2.3.…”
Section: The Cut-off Line Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim [15] used this method to give a sharp estimate on the k-core threshold of Erdős-Rényi random graphs. It turns out that the method can also be very useful in the study of G(n, µ) as shown in [2]. In this subsection, we introduce the algorithm and derive some properties that are used in Sections 2.2 and 2.3.…”
Section: The Cut-off Line Algorithmmentioning
confidence: 99%
“…Our first goal is to derive estimates on H T . For our purpose, it is enough to have some cheap estimates as in [2], nevertheless sharper ones can be found in [15]. We first make the following simple observation.…”
Section: The Cut-off Line Algorithmmentioning
confidence: 99%
“…The critical value is positive on Galton-Watson trees with tails thinner than the subexponential distribution. Recently Shankar Bhamidi, Danny Nam, Oanh Nguyen and Allan Sly [2] proved that Theorem 2. Consider the contact process on the Galton-Watson tree with offspring distribution D. If E(exp(cD)) < ∞ for some c > 0, then λ 1 > 0.…”
Section: Galton-watson Treesmentioning
confidence: 99%
“…By contrast, if the offspring distribution ξ has an exponential tail, i.e., Ee cξ < ∞ for some c > 0, Bhamidi and the authors [2] showed that there is an extinction phase: λ gw 1 (ξ) ≥ λ 0 (ξ) for some constant λ 0 (ξ) > 0. Our first main result derives the first-order asymptotics on λ gw 1 (ξ) for ξ concentrated around its mean, which turns out to have the same form as (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…
Recent progress in the study of the contact process [2] has verified that the extinctionsurvival threshold λ1 on a Galton-Watson tree is strictly positive if and only if the offspring distribution ξ has an exponential tail. In this paper, we derive the first-order asymptotics of λ1 for the contact process on Galton-Watson trees and its corresponding analog for random graphs.
…”
mentioning
confidence: 99%